Traumatic and Knowledge on Self Efficacy During The Postpartum Recovery Period - Girsang, Bina Melvia; Eqlima Elfira; Evi Indriani Br Karo; Ismayadi (Caring: Indonesian Journal of Nursing Science, 2023)
Information provision and postpartum care that is less than optimal is a problem that is often overlooked. The number of respondents based on the calculation of the sample size was 150 people, while the number of samples in this study were 134 postpartum mothers. The sample selection was carried out according to the probability sampling technique. Postpartum mothers were surveyed using a questionnaire about the history of childbirth trauma, the knowledge of postpartum mothers about self-care during the postpartum period, and the level of self-efficacy of postpartum mothers. The results of the study showed several factors that could affect the mother's self-efficacy in postpartum recovery, namely age (26.14 (4.96); p = 0.00), traumatic experience during childbirth (1.86 (0.34); p = 0.000), and mother's occupation (1.597 (0.49); p = 0.02), and knowledge (4.38 (1.68); p = 0.000). Nurses need to provide prenatal health education to increase women's beliefs about their behavior during labor and postpartum recovery.